Mobility of the creative class and city attractiveness: A case study of Chinese animation workers - Dai, J.; Zhou, S.; Keane, Michael; Huang, Q. (2012)
The paper investigates the geographical mobility of creative workers in China, focusing on the authors' survey of workers in the animation industry. More specifically, the authors use the Reilly-Converse model and GIS tools to probe the locational choices of Chinese animation workers in Beijing and Shanghai by analyzing such factors of spatial attractiveness as home town, place of residence, and university from which the worker graduated. The paper compares the creative milieus in Beijing and Shanghai, and demonstrates that the "personal trajectory" of human capital is a key determinant of occupational location. The results of the authors' survey highlight the limitations of Richard Florida's 3T theory in the Chinese context.